Effect of prophylactic training on potential risk factor for future ACL injury - Petersen, M. B.; Bencke, J.; Lauridsen, H. B.; Curtis, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Young female soccer and handball players are at highest risk of sustaining an ACL-injury (Lind et al. 2009). Most non-contact ACL-injuries occur during sidecut manoeuvres (Olsen et al. 2004). A potential risk factor during sidecutting is a high vastus lateralis (VL) and low semitendinosus (ST) neuromuscular activity just before foot strike (Zebis et al. 2009). The present study examined the effect of 12 weeks of prophylactic training on the VL-ST pre-activity difference in young female athletes. Methods: Forty young female soccer and handball players (age 15.7 ± 0.5 years, weight 63.7 ± 10.8 kg, height 168 ± 5.6 cm) were randomized to prophylactic neuromuscular training (NMT, n=20) or control group (Con, n=20). In the NMT-group, 12 weeks of prophylactic training (Olsen et al. 2005) was implemented 3/week while the Con-group continued their regular warm up exercises. VL and ST muscle activity (EMG) was measured during a sidecutting manoeuvre in the 50 ms time interval prior to foot strike on a force plate (AMTI). EMG activity was normalized to peak EMG amplitude recorded during MVC. A per protocol analysis was performed on players who remained uninjured and who had undergone at least 10 weeks of full training and match play, (NMT, n=15) and (Con, n=10). Results: In the Con-group neuromuscular pre-activity of the ST was significantly lowered (P=0.011) and the VL-ST pre-activity difference significantly increased (P=0.046) compared with the NMTgroup. In the Con-group, seven players suffered an injury in the lower extremity compared to one player in the NMT-group (P=0.04). Discussion: Twelve weeks of prophylactic training prevented a decrease in the neuromuscular activity of the ACL-agonist ST in young female soccer and handball players. Further, the increase in VL-ST pre-activity difference in the Con-group implies a reduced capacity for knee joint stabilization during high-risk movements like the sidecut manoeuvre.